Arbil, Föderale Region Kurdistan/Irak: Die Arbeiten der Jahre 2012 und 2013 - van Ess, Margarete; Hausleiter, Arnulf (e-Forschungsberichte des DAI, 2023)
Excavations in the city of Arbil have been conducted by the Directorate of Antiquities and the German Archaeological Institute since 2009. At some 0.5 km west of the Citadel, an ancient mound located in the former lower town area of the city, revealed occupation remains of the Neo-Assyrian to Post-Assyrian periods (8th to 6th century BC) with an almost intact vaulted grave chamber, as well as remains of a burial ground, the latter probably used until the Sassanian period (6th century AD).